Affective Scaffoldings as Habits: A Pragmatist Approach - Candiotto, Laura; Dreon, Roberta (Frontiers in Psychology, 2021)
In this paper, we provide a pragmatist conceptualization of affective habits as relatively flexible ways of channeling affectivity. Our proposal, grounded in a conception of sensibility and habits derived from John Dewey, suggests understanding affective scaffoldings in a novel and broader sense by re-orienting the debate from objects to interactions. We claim that habits play a positive role in supporting and orienting human sensibility, allowing us to avoid any residue of dualism between internalist and externalist conceptions of affectivity. We provide pragmatist tools for understanding the environment's role in shaping our feelings, emotions, moods, and affective behaviors. However, we contend that in addition to environment, the continuous and recursive affective transaction between agent and environment (both natural and cultural) are also crucially involved. We claim that habits are transformative, which is especially evident when we consider that emotions are often the result of a crisis in habitual behavior and successively play a role in prompting changes of habits. The final upshot is a conceptualization of affective habits as pervasive tools for feelings that scaffold human conduct as well as key features in the transformation of behaviors.